OptiSCI: a Visual Environment to Optimize the Placement of Shared Memory Segments on a SCI Cluster - Ávila, Rafael B.; De Rose, César A. F.; Ferreto, Tiago; Barreto, Marcos E.; Navaux, Philippe O. A.; Heiβ, Hans-Ulrich; Hexsel, Roberto A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
The Scalable Coherent Interface (SCI) is an IEEE interconnection standard which is becoming widely used for the construction of parallel clusters of workstations. SCI provides a hardware-supported common address space shared by the computing nodes, enablin the use of shared-memory as a distributed communication mechanism. Due to the strong NUMA characteristic of SCI-based clusters, the placement of shared segments among the nodes has to be carefully planned, in order to minimize the cost of network communication latencies. In this paper we present a visual tool, OptiSCI, to help in the task of placing shared memory segments onto a SCI cluster with respect to such communication cost. OptiSCI is composed of a graphical modelling tool and a hardware simulator which makes use of a detailed cost model of SCI clusters in order to produce reliable results. At the end the tool is validated against a real implementation of a parallel application on a Linux SCI cluster.